2016
DOI: 10.18433/j3z32f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macrolide Antibiotics on Th1 Cell and Th2 Cell Development Mediated by Langerhans Cells

Abstract: -Background:It is well known that Langerhans cells (LCs) work as the primary orchestrators in the polarization of the immune milieu towards a T helper type 1 (Th1) or a Th2 immune response. In this study, we investigated the effects of macrolide antibiotics on Th1 cell and Th2 cell development mediated by LCs. Methods: LC-like dendritic cells (LDCs) were generated from mouse bone marrow cells and used as substitutes for LCs. Mice were primed with ovalbumin (OVA) peptide-pulsed LDCs, which had been treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Furthermore, TNCB treatment induced expression of the Th1 cytokine, IFN-γ, in the lymph nodes of NC/Nga mice, and its expression was inhibited by the topical application of josamycin. This might also explain the results of our previous study (12) in which LCs treated with josamycin showed inhibition of not only Th2 cell development but also Th1 cell development in lymph nodes through down-regulation of CD86. On the other hand, elevation of IFN-γ and IL-4 expression in TNCB-treated NC/Nga mice was observed in skin lesions, similarly to human AD lesions (17), and topical application of josamycin inhibited the expression of both IFN-γ and IL-4.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Furthermore, TNCB treatment induced expression of the Th1 cytokine, IFN-γ, in the lymph nodes of NC/Nga mice, and its expression was inhibited by the topical application of josamycin. This might also explain the results of our previous study (12) in which LCs treated with josamycin showed inhibition of not only Th2 cell development but also Th1 cell development in lymph nodes through down-regulation of CD86. On the other hand, elevation of IFN-γ and IL-4 expression in TNCB-treated NC/Nga mice was observed in skin lesions, similarly to human AD lesions (17), and topical application of josamycin inhibited the expression of both IFN-γ and IL-4.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, our previous study showed that S. aureus strains isolated from the lesional skin of AD patients were susceptible to josamycin (12). Since the skin of most AD patients shows superficial S. aureus colonization and barrier disruption due to a decrease of filaggrin (23), bacterial products such as staphylococcal enterotoxins, lipoteichoic acid and peptidoglycan would be expected to penetrate the skin and induce the production of Th2 cells and chemokines, which in turn would induce a Th2 immune response and augment skin inflammation (1,(4)(5)(6)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations